Evaluation of the Emotional Impacts of the Notre Dame Cathedral Fire and Restoration on a Population Sample - Miguel Ángel Maté-González; Cristina Sáez Blázquez; Noelia Gutiérrez-Martín; Myriam Lorenzo Canales (Heritage, 2025)
The fire at the Notre Dame Cathedral accentuated the sense that this architectural building is a symbol of unity and identity for the population. This symbol extends beyond its French and Christian origins, reflecting the universal nature of cultural heritage, which has the extraordinary ability to unite people across nations, transcending ideologies, religions, and political divisions. The reopening of the Notre Dame Cathedral marks a profound milestone in the preservation of cultural heritage, embodying resilience, restoration, and the enduring significance of shared human history. This research examines the impacts of the restoration of the cathedral at national and global scales through the implementation of questionnaires to visitors to the cathedral’s inauguration. The restoration process, which gained extensive media coverage, not only revived the cathedral’s architectural grandeur but also sparked international discussions about heritage conservation. Through an analysis of the questionnaire results for different factors, this study highlights the complexities of managing a monumental heritage of this magnitude in a globalized world. It reflects the ethical, financial, and social challenges involved in major restoration projects, using Notre Dame as a paradigmatic example. The paper concludes that the reopening of the cathedral is not only a triumph of physical restoration but also a testament to humanity’s resilience in the face of adversity. It serves as a powerful reminder of the importance of safeguarding cultural heritage for future generations while fostering a sense of collective responsibility.